Management of Tiara Dance Studio in Banjarnegara Regency - Dina Ayu Sabila (Jurnal Seni Tari, 2025)
This research aims to describe and analyze the management of Sanggar Tari Tiara in Banjarnegara Regency in maintaining its existence and developing traditional and creative dance arts. This study uses a qualitative approach with a descriptive method. Data collection techniques include observation, interviews, and documentation involving the studio head, trainers, and administrators. The results show that the management of Sanggar Tari Tiara encompasses four main functions: planning, which is proven to be systematic and adaptive and focuses on human resource (HR) recruitment; organizing, which is carried out to divide tasks and responsibilities; implementing, which aims to divide age and experience categories in conducting learning; and supervising, which aims to observe the implementation of activities, assess results, and evaluate after training and events, all of which are carried out synergistically and continuously. The studio's success in achieving various local to international accomplishments is inseparable from its structured management, the commitment of its members, and collaboration with art communities and local government. This research affirms that good management is key to the preservation and development of local arts  and culture.